Tectonic and sedimentary history of the Mid-Natal Valley (S.W. Indian Ocean) - Goodlad, Stephen W; Goodlad, Stephen W (Department of Geological Sciences, 2017)
The Natal Valley is a sediment-filled marine basin situated between the east coast of southern Africa (Natal) and the Mozambique Ridge. Geophysical and sedimentological techniques are used in a broad geological study of the mid Natal Valley. Major emphasis is directed to: (a) basin history and tectonic evolution; (b) seismic stratigraphy of the basin fill; (c) recent sedimentary processes and responses. General basin morphology is defined by five major physiographic provinces: continental shelf and slope, Tugela Cone, Central Terrace, Mozambique Ridge and deep basin plain. Thinned (20-25 km) continental crust, attenuated and subsided in response to Gondwana rifting and drifting, underlies the Central Terrace, Tugela Cone and Mozambique Ridge. Southern margins of the Central Terrace and Tugela Cone are cored by a series of subsea floor ridge and pinnacle complexes (Naude, East Tugela and South Tugela Ridges). Geochemical analyses of East Tugela Ridge basalts suggest a transitional origin but with continental affinities. These volcanic marginal ridges may approximately delineate the continental-oceanic crust boundary (COB) in the Natal Valley. To the south, the deep basin plain is underlain by oceanic crust.